2013
DOI: 10.1007/s11682-013-9232-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributions to changes of fiber tracts of ventral visual stream in 22q11.2 deletion syndrome

Abstract: Patients with 22q11.2 deletion syndrome (22q11.2DS) represent a population at high risk for developing schizophrenia, as well as learning disabilities. Deficits in visuo-spatial memory are thought to underlie some of the cognitive disabilities. Neuronal substrates of visuo-spatial memory include the inferior fronto-occipital fasciculus (IFOF) and the inferior longitudinal fasciculus (ILF), two tracts that comprise the ventral visual stream. Diffusion Tensor Magnetic Resonance Imaging (DT-MRI) is an established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 64 publications
0
21
1
Order By: Relevance
“…50 Patients with 22q.11.2 deletion syndrome, who are at genetic high risk for developing schizophrenia, also showed lower FA values in left IFOF. 51 Together, these data suggest that the observed WM tract alterations may represent a risk factor for development of psychosis.…”
Section: Discussionmentioning
confidence: 83%
“…50 Patients with 22q.11.2 deletion syndrome, who are at genetic high risk for developing schizophrenia, also showed lower FA values in left IFOF. 51 Together, these data suggest that the observed WM tract alterations may represent a risk factor for development of psychosis.…”
Section: Discussionmentioning
confidence: 83%
“…However, it has also been shown that AD (and FA) increase during adolescence in typical youth (Kubicki et al, 2013; Kumar et al, 2013; Wu et al, 2014) suggesting that axonal coherence continues to improve during adolescence. Interestingly, in the case of 22q11.2DS improvement to normal levels might not be reached, as a DTI study of adults with 22q11.2DS found that FA and AD remain reduced (Kikinis et al, 2013; Kikinis et al, 2012). This implies that white matter pathology in 22q11.2DS may involve both early aberrant developmental and ongoing deleterious processes.…”
Section: Discussionmentioning
confidence: 99%
“…These areas also show aberrant connectivity in individuals with schizophrenia. Other significant DTI findings in 22q11.2DS include abnormalities within fibers of the visual ventral stream and a significant correlation between FA values in left parietal areas and arithmetic subtest scores (Barnea-Goraly et al, 2005; Kikinis et al, 2013). In addition, children with 22q11.2DS have higher parietal FA values that are related to poorer performance on an attentional counting task, thereby suggesting a different developmental trajectory related to disruption in parietal connectivity via the superior longitudinal fasciculus (SLF; Simon et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Already in 1996, Aloia and colleagues proposed that the disruption of semantic networks have potential implications for the origin of “thought disorder” in schizophrenia 24 . Adding to this hypothesis, patients with 22q11.2 deletion syndrome, who are genetically at high risk for developing schizophrenia, showed lower FA values in left IFOF 25 . Furthermore, DeRosse and colleagues found that lower FA proximal to the SLF and corticospinal tract bilaterally, and left IFOF and left inferior longitudinal fasciculus (ILF), were associated with higher levels of psychotic-like experiences in otherwise healthy volunteers 26 .…”
Section: Discussionmentioning
confidence: 94%